Assessment of drought impacts on water quantity and quality: Implications for water resources and the Severn Thames Transfer - Lee, J (2020)
Water resource management planners are increasingly aware of the effects that climate change and population growth will have on current, conventional water resources management plans. This requires an understanding of the vulnerability and sustainability of the current water supply options and the development of new water resource options to cope with more intense, longer, and more frequent droughts. Water stress in South East England is projected to increase over the next planning horizon, and water planners are continuously looking to develop drought management options with neighbouring water companies to transfer water cross basins to alleviate some of the water stress. The Severn-Thames Transfer is actively discussed as the preferred investment scheme to secure water supply in the Thames basin in the United Kingdom. In terms of inter-basin water transfers, understanding surplus water availability from the donor catchment is a vital factor. Thus thorough exploration of the wide range of extreme events in both donor and receiving catchments must be incorporated into the feasibility assessments. Together with consideration of water quantity resilience in the system, water quality risks associated with mixing two waters must be addressed prior to implementation.